Produzione dell'Architettura tra tecniche e progetto / Architectural Planning between build and design techniques Ricerca e innovazione per il territorio / Glocal oriented research and innovation Materiali del V Seminario OsDotta - LAURIA, Massimo (Scuole di dottorato, 2010)
The V Seminar OsDotta, that took place in Reggio Calabria, at the Department DASTEC, in September 2009, focused the debate on what type of contribution the Technology of the Architecture can offer, today, to the education of an architect, designer and researcher. The themes proposed for the three working tables - Techniques Materials Design - Techniques Processes Design - Techniques Morphologies Design - have been set out through reference frameworks, syntheses of the preliminary activities, results and products elaborated during the workshop. From these works some disciplinary criticalities and potentiality come out, interfacing themselves with checks on outside spendable aspects of the acquired competences and with the analysis introduced by the international referees.